Pengaruh Gaya Hidup, Kontrol Diri, Literasi Keuangan Dan Persepsi Resiko Terhadap Tren Penggunaan Paylater Dikalangan Mahasiswa - Anggiaputri, Ajeng Rizky; Efriyenti, Dian (Cattleya Darmaya Fortuna, 2025)
Paylater services are now a common element for online purchasing and other consumer activities in the digital age. But what effects do lifestyle, self-control, financial literacy, and risk perception have on the trend of students using Paylater? 97 students in Batam City who have used or are presently utilizing Paylater services will get questionnaires as part of this study's quantitative approach to answering this topic. According to the analysis, the trend of Paylater usage is significantly and favorably influenced by the independent factors of lifestyle, self-control, financial literacy, and risk perception. Furthermore, when considered collectively, these four characteristics exhibit a significant influence. These findings highlight the significance of improving financial literacy and better financial management to encourage prudent financial decision-making, even while students are prone to using Paylater impulsively. It is intended that this study will be used as a guide for initiatives aimed at enhancing students' financial literacy and encouraging responsible attitudes toward digital financial services.